2022
DOI: 10.3390/vaccines10050663
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Anti-SARS-CoV-2 Vaccine in Patients with Systemic Lupus Erythematosus: A Multicentre Cohort Study

Abstract: Vulnerable subjects, including systemic lupus erythematosus (SLE) patients, have been prioritised to receive anti-SARS-CoV-2 vaccines. Few data about the safety of these vaccines in SLE are available. The aim of our study is to investigate the safety of anti-SARS-CoV-2 vaccines in SLE. We included 452 SLE patients, referring to seven tertiary centres, who were immunised. A total of 119 (26%) reported side effects (SE) after the first and/or the second shot (the most frequent SE were fever, local reaction, fati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…Various studies have reported associations between lupus disease flares and mRNA COVID-19 vaccination ( Supplementary Table S3 ) [ 25 , 26 , 27 , 28 , 29 ] and two have focused on SLE patients [ 25 , 26 ]. A study involving 183 SLE patients reported that 11 (6%) patients experienced flares following vaccination, most of which were mild and constituted symptoms such as joint pain, skin rash, fatigue, muscle aches and mouth ulcers [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have reported associations between lupus disease flares and mRNA COVID-19 vaccination ( Supplementary Table S3 ) [ 25 , 26 , 27 , 28 , 29 ] and two have focused on SLE patients [ 25 , 26 ]. A study involving 183 SLE patients reported that 11 (6%) patients experienced flares following vaccination, most of which were mild and constituted symptoms such as joint pain, skin rash, fatigue, muscle aches and mouth ulcers [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study involving 183 SLE patients reported that 11 (6%) patients experienced flares following vaccination, most of which were mild and constituted symptoms such as joint pain, skin rash, fatigue, muscle aches and mouth ulcers [ 25 ]. A multicentre cohort study of 452 SLE patients who had received COVID-19 vaccination found that 4% of patients flared after immunisation, with musculoskeletal, constitutional symptoms and renal being the most common types of flare; however, none of the disease flares required hospitalisation [ 26 ]. It is worth noting that new-onset SLE after mRNA COVID-19 vaccination has been described in various case reports, raising the plausibility of an association between induced autoimmunity and mRNA vaccination [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune medications given to the patients included alemtuzumab [29,34,48,66], abatacept [8,33,35,39,47,57,58,63,[72][73][74][75]94,98], anti-CD20/-B cell depleting therapy [8,29,[32][33][34][35]37,[39][40][41]43,45,[47][48][49][52][53][54][55]57,60,[62][63][64][65][66]72,74,75,87,89,92,94,[96]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Initial studies on the 2021 original COVID vaccine series administered to SLE patients demonstrated clinical efficacy with impaired but generally sufficient immunogenicity [11,12 ▪ ]. Despite theoretical risks, patient concerns, and case reports, vaccination rarely precipitated severe flares in larger studies [12 ▪ ,13–18].…”
Section: Special Implications Of Covid Vaccination For Systemic Lupus...mentioning
confidence: 99%